Manifestations of Cytomegalovirus Infection 2013
DOI: 10.5772/54907
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus (HCMV) Infection in Sub-Saharan Africa

Abstract: . HCMV seroprevalenceThere have been over published studies which present HCMV IgG seroprevalence data for sub-Saharan Africa patient groups and cohorts of healthy blood donors Table . Up to eight different serology assays were used and older pre-ELISA methods might have slightly underestimated prevalence [ ]. Antibodies to HCMV are generally present in high titres in seropositive individuals, so the use of different assays is unlikely to have had a major effect [ ]. Hence, comparing these studies is primarily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 138 publications
0
4
0
Order By: Relevance
“…[ 56 , 57 ] One review that included over 25 studies from sub-Saharan African countries found weighted average CMV IgG seroprevalence rates in HIV-infected and HIV-uninfected adult patients to be 80.0% (range 59%-100%) and 79.3% (range 55%-97%), respectively. [ 58 ] Thus, the absence of CMV data in our study remains a limitation, but we do not believe that CMV infection is significantly affecting our finding that HIV infection is an independent predictor associated with shorter telomere length due to the similar rates of CMV infection found in numerous studies from sub-Saharan Africa.…”
Section: Discussionmentioning
confidence: 73%
“…[ 56 , 57 ] One review that included over 25 studies from sub-Saharan African countries found weighted average CMV IgG seroprevalence rates in HIV-infected and HIV-uninfected adult patients to be 80.0% (range 59%-100%) and 79.3% (range 55%-97%), respectively. [ 58 ] Thus, the absence of CMV data in our study remains a limitation, but we do not believe that CMV infection is significantly affecting our finding that HIV infection is an independent predictor associated with shorter telomere length due to the similar rates of CMV infection found in numerous studies from sub-Saharan Africa.…”
Section: Discussionmentioning
confidence: 73%
“…Recent prospective studies and careful review of some older but overlooked studies, has lead to a growing awareness of the importance of HCMV infections in high seroprevalence settings [11][12][13], as a major cause of mortality in HIV-infected children [14,15] and as a cause of developmental delay [5] and hearing loss [16][17][18] in children through either congenital or early infant infections, with maternal HIV infection and lower CD4 count associated with higher prevalence of congenital infection [15,19]. Human herpesvirus 6A (HHV-6A), Human herpesvirus 6B (HHV-6B) and Human herpesvirus 7 (HHV-7)) have been less well studied in sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Determination of positive and negative samples for the presence of specific antibodies (IgM and IgG) for CMV and rubella was done by ELISA system depending on the cut-off values of standard positive and negative controls as shown in table (1).Equivocal CMV IgM or IgG results may occur during acute infection or may be due to non-specific binding reactions (12), thus, Samples showed equivocal titers were considered negative for the presence of specific antibody. (14).…”
Section: Resultsmentioning
confidence: 99%